Intelligent careers and human resource management practices: qualitative insights from the public sector in a clientelistic culture - Maria Mouratidou; Mirit K. Grabarski; William E. Donald (Journal of Work-Applied Management)
Purpose – The purpose of this study is to empirically test the intelligent career framework in a public sector setting in a country with a clientelistic culture to inform human resource management strategies. Design/methodology/approach – Based on a qualitative methodology and an interpretivist paradigm, 33 in-depth interviews were conducted with Greek civil servants before the COVID-19 pandemic. The interview recordings were subsequently transcribed and coded via a blend of inductive and deductive approaches. Findings – Outcomes of the study indicate that in a public sector setting in a country with a clientelistic culture, the three dimensions of knowing-whom, knowing-how and knowing-why are less balanced than those reported by findings from private sector settings in countries with an individualistic culture. Instead, knowing-whom is a critical dimension and a necessary condition for career development that affects knowing-how and knowing-why. Originality/value – The theoretical contribution comes from providing evidence of the dark side of careers and how imbalances between the three dimensions of the intelligent career framework reduce work satisfaction, hinder career success and affect organisational performance. The practical contribution offers recommendations for human resource management practices in the public sector, including training, mentoring, transparency in performance evaluations and fostering trust.